Impact of Modified Frailty Index on Readmissions Following Surgery for NSCLC - Tamburini, Nicola; Dolcetti, Francesco; Fabbri, Nicolò; Azzolina, Danila; Greco, Salvatore; Maniscalco, Pio; Dolci, Giampiero (The Thoracic and Cardiovascular Surgeon, 2024)
Background Analyzing the risk factors that predict readmissions can potentially lead to more individualized patient care. The 11-factor modified frailty index is a valuable tool for predicting postoperative outcomes following surgery. The objective of this study is to determine whether the frailty index can effectively predict readmissions within 90 days after lung resection surgery in cancer patients within a single health care institution.Methods Patients who underwent elective pulmonary resection for nonsmall cell lung cancer (NSCLC) between January 2012 and December 2020 were selected from the hospital's database. Patients who were readmitted after surgery were compared to those who were not, based on their data. Propensity score matching was employed to enhance sample homogeneity, and further analyses were conducted on this newly balanced sample.Results A total of 439 patients, with an age range of 68 to 77 and a mean age of 72, were identified. Among them, 55 patients (12.5%) experienced unplanned readmissions within 90 days, with an average hospital stay of 29.4 days. Respiratory failure, pneumonia, and cardiac issues accounted for approximately 67% of these readmissions. After propensity score matching, it was evident that frail patients had a significantly higher risk of readmission. Additionally, frail patients had a higher incidence of postoperative complications and exhibited poorer survival outcomes with statistical significance.Conclusion The 11-item modified frailty index is a reliable predictor of readmissions following pulmonary resection in NSCLC patients. Furthermore, it is significantly associated with both survival and postoperative complications.
Keywords: frailty; thoracic surgery; risk stratification; surgical outcomes; risk models